2016
DOI: 10.1038/srep27289
|View full text |Cite
|
Sign up to set email alerts
|

High hydrostatic pressure adaptive strategies in an obligate piezophile Pyrococcus yayanosii

Abstract: Pyrococcus yayanosii CH1, as the first and only obligate piezophilic hyperthermophilic microorganism discovered to date, extends the physical and chemical limits of life on Earth. It was isolated from the Ashadze hydrothermal vent at 4,100 m depth. Multi-omics analyses were performed to study the mechanisms used by the cell to cope with high hydrostatic pressure variations. In silico analyses showed that the P. yayanosii genome is highly adapted to its harsh environment, with a loss of aromatic amino acid bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
43
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 59 publications
(90 reference statements)
8
43
1
4
Order By: Relevance
“…The transcription levels of the genes in module III (PYCH_15220 to PYCH_15270) were up-regulated under low pressure (0.1 MPa, 95°C) and high pressure (70 MPa, 95°C) conditions compared with the optimal conditions (52 MPa, 95°C). These results were consistent with the transcriptomic study of P. yayanosii , in which it was shown that the transcription levels of PYCH_15210, PYCH_15270, and PYCH_15290 in PYG1 under 20 and 80 MPa conditions were higher than those observed under 52 MPa conditions (Michoud and Jebbar, 2016). Under high temperature stress, the expression of PYCH_15260 and PYCH_15270 showed obvious up-regulation at 100°C.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The transcription levels of the genes in module III (PYCH_15220 to PYCH_15270) were up-regulated under low pressure (0.1 MPa, 95°C) and high pressure (70 MPa, 95°C) conditions compared with the optimal conditions (52 MPa, 95°C). These results were consistent with the transcriptomic study of P. yayanosii , in which it was shown that the transcription levels of PYCH_15210, PYCH_15270, and PYCH_15290 in PYG1 under 20 and 80 MPa conditions were higher than those observed under 52 MPa conditions (Michoud and Jebbar, 2016). Under high temperature stress, the expression of PYCH_15260 and PYCH_15270 showed obvious up-regulation at 100°C.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, HHP increases amino acid requirements in T. barophilus MP (Cario et al, 2015). Several amino acid biosynthesis pathways are missing in the P. yayanosii genome (Michoud and Jebbar, 2016). PYCH_15260 is annotated as a class II glutamine amidotransferase.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effect of high hydrostatic pressure on growth and metabolism is less frequently investigated due to the difficulties involved in the experimental design (Takai et al, 2008). For example, previous studies of piezophilic micro-organisms have suggested that energy production and central metabolism-related genes appear to be overexpressed under high hydrostatic pressures (Amrani et al, 2014;Cario, Jebbar, Thiel, Kervarec, & Oger, 2016;Michoud & Jebbar, 2016;Pradel et al, 2013;Vannier, Michoud, Oger, Marteinsson, & Jebbar, 2015). A recent study involving high-pressure culturing of a piezophilic and chemolithoautotrophic epsilonproteobacterium (Nautilia sp.…”
mentioning
confidence: 99%
“…In this study, we report a novel ferritin (PcFn) from the hyperthermophile Pyrococcus yayanosii CH1, which was isolated from a vent eld at a depth of 4100 m and characterized as the rst obligate piezophilic hyperthermophilic microorganism (optima of 52 MPa and 98 C). [33][34][35] According to these extremely harsh living conditions, we hypothesized that the ferritin and magnetoferritin from P. yayanosii CH1 might be resistant to high temperatures. To test this hypothesis, we cloned and overexpressed the PcFn gene from hyperthermophile P. yayanosii CH1 in Escherichia coli (E. coli), and successfully used the puried PcFn protein for biomimetic synthesis of magnetoferritin (M-PcFn 5000 ), with a loading factor of 5000 Fe/cage.…”
Section: Introductionmentioning
confidence: 99%